Very low level viraemia and risk of virological failure in treated HIV‐1‐infected patients. Issue 3 (1st August 2016) - Teira, R; Vidal, F; Muñoz‐Sánchez, P; Geijo, P; Viciana, P; Ribera, E; Domingo, P; Castaño, M; Martínez, E; Roca, B; Puig, T; Estrada, V; et al.
Abstract : Objectives: The aim of the study was to investigate whether very low level viraemia (VLLV) (20–50 HIV‐1 RNA copies/mL) was associated with increased risk of virological failure (VF) as compared with persistent full suppression (< 20 copies/mL). Methods: From the VACH Cohort database, we selected those patients who started antiretroviral therapy (ART) after January 1997 and who achieved effective viral suppression [two consecutive viral loads (VLs) < 50 copies/mL] followed by full suppression (at least one VL <20 copies/mL). We carried out survival analyses to investigate whether the occurrence of VLLV rather than maintaining full suppression at < 20 copies/mL was associated with virological failure (two consecutive VLs > 200 copies/mL or one VL > 200 copies/mL followed by a change of ART regimen, administrative censoring or loss to follow‐up), adjusted for nadir CD4 cell count, sex, age, ethnicity, transmission group, type of ART and time on effective suppression at < 50 copies/mL. Results: Of 21 480 patients who started ART, 13 674 (63.7%) achieved effective suppression at < 50 copies/mL, of whom 4289 (31.4%) further achieved full suppression at < 20 copies/mL after May 2009. A total of 2623 patients (61.1%) remained fully suppressed thereafter, while 1666 had one or more episodes of VL detection > 20 copies/mL (excluding virological failure). A total of 824 patients had VLLV after suppression at < 20 copies/mL. VLLV was not associated with virological failure as compared with persistent full suppression [hazard ratio (HR) 0.67; 95% confidence interval (CI) 0.44–1.00], independently of the number of blips recorded (from one to 18). Conclusions: In our population of HIV‐infected patients on ART who achieved viral suppression at < 20 copies/mL, the risk of virological failure was no different for patients who remained fully suppressed compared with those who experienced subsequent episodes of VLLV.